(untitled) (Research, Society and Development, 2021)
Dulce de leche is a product very appreciated by its consumers, for being a food rich in nutrients and with high energy value. On the other hand, many people have restrictions to consume it, due to its high glycemic index. Aiming to develop viable formulations of diet dulce de leche, using xylitol as a sucrose replacement with goat milk bovine milk. Four pasty dulce in leche formulations were developed: bovine milk with sucrose (F1), bovine milk with xylitol (F2), goat milk with sucrose (F3) and goat milk with xylitol (F4). Bromatological analysis was performed to determine the macronutrients and the Acceptance Test was used for the sensory analysis with application of the 9-point hedonic scale. In the bromatological analysis, the samples F1 and F3 had the highest carbohydrate contents, with 79.40% and 78.87% respectively, while the samples F2 and F4 had a carbohydrate content of 12.24% and 12.25%, respectively. This difference had a direct impact on the determination of the Total Caloric Value (TCV) of the samples, since F1 and F3 formulations were the most caloric. As for the sensory analysis, all formulations were considered well accepted, as they presented an acceptability index above 70%. The use of xylitol as a substitute proved to be viable. The dulce de leche with this sweetener in its composition were less caloric and the formulations were well accepted by the tasters. Therefore, it is possible to enable the use of this sweetener in the food industry.